Efektivitas Bimbingan Kelompok dengan Teknik Problem Solving untuk Meningkatkan Keterampilan Belajar Siswa Madrasah Aliyah Negeri 3 Medan - Adinda Salsameywa Putri; Alfin Siregar; Ali Daud Hasibuan (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This research aims to see whether group guidance using problem solving techniques can improve students' learning skills at Madrasah Aliyah Negeri (MAN) 3 Medan. This research uses quantitative methods with a quasi-experimental approach, non-equivalent control group design. In this design, both groups (experimental and control) underwent an initial test (pre-test) and a final test (post-test), but only the experimental group was given treatment, while the control group was not given treatment. The research population consisted of students in class X-1 (30 students) and X-2 (30 students). The sample was selected using a purposive sampling method, with a total of 16 students who had low learning skills, namely 8 students from the experimental group (class X-2) and 8 students from the control group (class X-1). The research instrument is a learning skills questionnaire with 26 statements whose validity and reliability have been tested. Data were analyzed using the T-test. The T-test results showed that the experimental group experienced an increase in learning skills, with a significance value of 0.000 < 0.05. This means that problem solving techniques are effective in improving students' learning skills. In contrast, the control group did not show a significant increase in learning skills, with a significance value of 0.022 > 0.05. The results of the independent sample t-test show a significance value (2-tailed) of 0.000 <0.05, which means there are differences in students' learning skills before and after being given services in the experimental group.